2023
DOI: 10.4236/fns.2023.143016
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oils as an Alternative to Antibiotics to Reduce the Incidence and Severity of Necrotic Enteritis in Broiler Chickens: A Short Review

Abstract: Due to the removal of antibiotic growth promoters (AGPs) and consumer pressure for antibiotic-free (ABF) or no antibiotics ever (NAE) poultry production, there is a need for sustainable alternatives to prevent disease in commercial poultry operations. Without AGPs, there has been a rise in diseases that were traditionally controlled by subtherapeutic levels of antibiotics in the diet. This has impacted the health of commercial poultry and has been a significant cost to poultry producers. To mitigate this, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 154 publications
0
1
0
Order By: Relevance
“…This effect is important for poultry health, as high cholesterol levels can lead to fatty liver disease and other metabolic disorders. Coles et al (2023) , however, suggested the use of curcumin in combination with essential oils to promote the health status of broiler chicken.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is important for poultry health, as high cholesterol levels can lead to fatty liver disease and other metabolic disorders. Coles et al (2023) , however, suggested the use of curcumin in combination with essential oils to promote the health status of broiler chicken.…”
Section: Introductionmentioning
confidence: 99%